2015
DOI: 10.1007/s10633-015-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern visual evoked potentials for identifying malingering

Abstract: The pattern VEP amplitude of 50' checkerboard size was useful to assess VA and can be helpful in discriminating malingering from real disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…This value of the VEP spatial frequency limit is likely to have the closest association with a clinical measurement of visual acuity since both are estimates of spatial threshold, although they have different physiological bases. 20,21 Our findings confirm this. The differences in maturation of the two measures can help forecast behavioural outcomes based on confirmation of some degree of visual pathway function in infancy using VEPs that mature early in comparison to behavioural acuity, which continues to develop later in preschool years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This value of the VEP spatial frequency limit is likely to have the closest association with a clinical measurement of visual acuity since both are estimates of spatial threshold, although they have different physiological bases. 20,21 Our findings confirm this. The differences in maturation of the two measures can help forecast behavioural outcomes based on confirmation of some degree of visual pathway function in infancy using VEPs that mature early in comparison to behavioural acuity, which continues to develop later in preschool years.…”
Section: Discussionsupporting
confidence: 88%
“…The smallest check width to produce a PRVEP may be termed the VEP spatial frequency limit. This value of the VEP spatial frequency limit is likely to have the closest association with a clinical measurement of visual acuity since both are estimates of spatial threshold, although they have different physiological bases 20,21 . Our findings confirm this.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It includes peak time and amplitude evaluation elements, with low variability across subjects and a strong relationship with VA. PRVEPs are mainly applied in patients who are unable or unwilling to complete a subjective VA examination and those with cognitive deficits. They are widely used in the assessment of optic neuropathy [ 1 3 ] and functional visual loss [ 4 ], in the identification of malingering [ 5 ], and in the early diagnosis and prognostication of multiple sclerosis [ 6 8 ]. Over the years, several reports have demonstrated that using the visual-evoked potential technique to detect the completeness of visual pathways has been widely recognized in ophthalmology [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, using AO to bypass the optical limits in VEP measurement is a new technique. It has been found that using the VEP measurements in visual performance tests appears to improve diagnostic power [9,10] . It prompts us to consider the new technique of integrating VEP measurements into an AO system.…”
mentioning
confidence: 99%